PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Valentino Ardian Perdana; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
The performance and accountabilty board of directors, foreign ownership and mecanism of governance continue to be a matter of concern. If a company with that corporate governance is not running well enough will inflict disperancy on reporting information in the financial statements with the fact that actual happen in the company. Good corporate governance mecanism is expected to minimize the agency problems so the financial performance can be increase. The purpose of this study is to examine the effect of corporate governance structure wich is internal corporate governace index, size of the board directors, and foreign ownership on financial performance proxied Return on Assets (ROA), Return on Equity (ROE), and Z-score in the banks that listed on the Indonesia Stock Exchange for period 2013 until 2016.The population of the study comprises firms listed on banking sector of the Indonesian Stock Exchange. The number of banking companies that listed in the Indonesian Stock Exchange during period 2013 until 2016 is 43. By using the techniques of purposive sampling, obtained a sample of 43 companies. The list companies for the period 2013-2016 is obtained from the website of Indonesian Stock Exchange.The findings show internal corporate governance index does not affect with financial performance proxied with ROA and ROE, but has an affect on Z-score. Boards of directors has an effect on financial performace proxied with ROA and ROE, in the other hand has a negative effect on Z-score. Foreign ownership has a negative effect on ROA and ROE, but does not affect with Z-score.